New species and record of Ptychoptera Meigen, 1803 (Diptera: Ptychopteridae) from China - Kang, Zehui; Xue, Zhaoxiang; Zhang, Xiao (Zootaxa, 2019)
Four new species of Ptychoptera Meigen, 1803 from China, P. emeica sp. nov., P. circinans sp. nov., P. lucida sp. nov. and P. separata sp. nov. are described and illustrated. One new record from China, P. yankovskiana Alexander, 1945 is redescribed and illustrated. A key to males of Ptychoptera species known to occur in China is presented.